THE INFLUENCE OF HUMAN RELATIONS AND THE PHYSICAL WORK ENVIRONMENT ON MORALE IN EMPLOYEES OF THE REGIONAL REVENUE AGENCY DELI SERDANG - Nahar Maganda Saragih; Rida Utami; Eduar Sinaga; Linda Sitepu (SEAN Institute, 2022)
In the maximum work process, every organization strives to produce the ultimate goal with organizational progress driven by workers in the organization. This progress is driven by the work enthusiasm possessed by members of the organization. Employee morale is also influenced by the relationship between employees, organizational culture and work environment. A good relationship between employees, namely fellow employees, can be a good driver or motivation for other employees regarding producing good work achievements. The physical work environment also fundamentally has an impact on employee morale where the conditions of the work environment that support each job will be able to trigger high morale, in practice the completeness or infrastructure that is qualified and supportive can create a motivation to be able to complete a job with high enthusiasm. Every agency always strives so that the performance of its employees can continue to be improved, for this reason, organizations need to find solutions to develop employee morale. This is important because with work enthusiasm, it will encourage employees to work better and more productively, so that organizational goals can be achieved. In this study, the results obtained from human relations and the physical work environment affect work enthusiasm either partially or simultaneously and have a coefficient of determination of 53% for work enthusiasm influenced by human relations and the physical work environment.